Spatial patterning and species coexistence: A case study using concentric circular vegetation patches in saline land - Yang, Ce; Zhu, Feng; Guo, Kai; Feng, Xiaohui; Liu, Xiaojing; Bezemer, T. Martijn (The Science of the total environment, 2024)
Spatial patterns in plant community structures within stressed ecosystems have drawn much attention in the field of ecology. However, the mechanisms underlying spatial formation and its impact on species coexistence and diversity remain controversial. In this study, we investigated concentric circular vegetation patches in coastal saline land, and analysed the spatial patterning of plant communities and associated soil physicochemical properties. Thereafter, we tested how the soil conditioned by plant communities from different locations within the vegetation patches influence the species growth and inter-specific competition. Our results show soil salinity enlarges in a centrifugal manner in horizontal direction in all patches. Soil salinity decreased and species diversity increased along with the increase of patch size. In addition, we found significant shifts in both the composition of plant communities and in soil physicochemical properties from outer to center. The results indicate that the pioneer species Suaeda salsa facilitated the subsequent species. However Suaeda salsa was inhibited and became inferior competitor in the soil conditioned by the subsequent species. We infer that the less-visible spatial patterns of soil physicochemical properties at small scales create ecological niches for specialized species, allowing them to coexist but not mix. We suggest that a trade-off between tolerance to salt stress and competitive ability under ameliorated conditions may underlie mechanisms of pattern formation in small scale. Our findings lend support to the idea that soil stress constraints community assembly and triggers spatial patterns, which, in turn, buffer the stress on plant communities and enhance species diversity. [Display omitted] •Soil salinity increases outward from the center in vegetation patches with self-spatial patterns.•Significant shifts in plant communities and soil salinity occur from the patch's edge to its center.•Pioneer species aid but become less competitive in soil conditioned by subsequent species.•Trade-off between salt tolerance and competitive ability may explain pattern formation.